Peculiarities of the PbTe nano-islet formation on BaF₂ substrate at "hot wall" epitaxy method investigated by atomic force microscopy - Sheremeta, T.I.; Prokopenko, I.V.; Lytvyn, P.M.; Lytvyn, O.S.; Vodop`yanov, V.M.; Bakhtinov, A.P.; Shyn`ko, E.I. (Functional Materials, 2007)
Peculiarities of PbTe nano-islet films formation on BaF₂ (111) fresh cleavages by hot wall epitaxy deposition have been investigated using atomic force microscopy. It has been shown that various growth mechanisms could be realized by selection of proper temperature regimes in the growth chamber: growth of three-dimensional nano-islets (VolmerWeber mechanism) and simultaneous growth of 2D layers (by Frank-van der Merwe) with 3D islets. The nano-islet shape and size can be controlled by temperature regimes and total amount of deposited material.